The relationship between family roles and medication adherence in tuberculosis patients at Puskesmas Ofa Padang, Mahondang, Asahan district, North Sumatra - Zuidah, Zuidah; Wati , Indah (Jurnal EduHealth, 2024)
Tuberculosis (TB) is a direct infectious disease caused by TB germs, namely Mycobacterium tuberculosis. The family's role is to directly participate in supervising pulmonary tuberculosis sufferers so that they take medication regularly until completion of treatment. The aim of this research is to determine the relationship between the role of the family and adherence to taking medication in tuberculosis patients at the Ofa Padang Mahondang Community Health Center, Asahan Regency, North Sumatra. The design of this research is descriptive, namely with a cross sectional study approach. The population in this study was 180 people using an incidental sampling technique for 2 weeks so that the sample in the study was 30 people. The Role of the Family in Tuberculosis Patients at Ofa Padang Mahondang District Health Center. Asahan, North Sumatra, it is known that the majority of respondents, 14 people (47%), have enough. The research results showed that the majority of medication compliance was in the medium category, 15 people (50%). The conclusion of this research is that there is a relationship between the role of the family and compliance with taking medication in tuberculosis patients at the Ofa Padang Mahondang District Health Center. Asahan North Sumatra with a significance value of 0.541 with correlation analysis there is a positive r value of 0.002. It is recommended that health workers include the role of the family in every counseling in the community